Maintenance of Rainwater Harvesting (RWH) system in Malaysia / Hafsah Yahaya - Hafsah, Yahaya (2012)
The application of Rainwater harvesting (RWH) system in Malaysia is still considered as a new phenomenon. However, with the support and effort of government in promoting the application of RWH in building, the number of building using the RWH is increased gradually. The system has been applied for various types of building such as housing, institutional and commercial. Even though the application of RWH is ongoing, there is no specific guideline in maintaining RWH. Maintenance performance is the key aspect in sustaining the RWH system. With the initial investment in installing the RWH, the organization must be able to monitor their investment in the form of maintenance performance. This will ensure the building owner achieve the value for money. The physical condition of RWH supports the ideas in tracking maintenance performance as a whole. Therefore, this research focuses on the improvement of maintenance management of RWH system with focusing on maintenance performance in Malaysia. This research used quantitative approach for data collection and data analysis. The conceptual framework of rainwater harvesting (RWH) system has been established before collection of the main data. There were two instruments implemented in this research namely physical condition survey and questionnaire survey. These instruments were developed based on the outlined conceptual framework. Condition survey has been carrying out to 16 buildings throughout the Peninsular Malaysia, and the data was analysed using CSP1 matrix. The results show only two buildings rated as dilapidated while fourteen buildings rated as good and fair. Questionnaire survey was distributed to three respondents for each building. A total of 48 respondents throughout Peninsular Malaysia were involved in the data collection. The data obtained later form a database and analysed using Statistical Package for Social Sciences (SPSS). The results of difficulties in maintaining RWH system in the building shows mean score less than 2.0, which consider as low. Both results demonstrated cross-combination finding via maintenance performance quadrant at the end of analysis and shows majority of buildings need improvement in terms of their maintenance management, while only two buildings regarded has as bad practice, which needs total refurbishment for the RWH system as well as the management. In conclusion, the physical condition of the RWH system is regarded good and safe implemented in the buildings. However, the maintenance of the system can be improved with a proper guideline and management policy by the organization involved. This is to ensure that the maximum value of installing the RWH system as well as ensuring the system performs to its intended design throughout the building’s lifetime.